Toward a social ecology of Johnson's types: exploring pathways to situational couple violence and coercive controlling violence among returning prisoners - McKay, Tasseli (Journal of family violence, 2024)
Purpose: Scholarship on the social and structural determinants of intimate partner violence (IPV) rarely differentiates between Johnson’s types in examining pathways to violent outcomes. This study applies Bronfenbrenner’s model to consider the etiology of Johnson’s types at multiple social-ecological levels. Method: To test the hypothesis that pathways from local social and structural conditions to IPV differ by type of IPV, I reanalyzed longitudinal data from a recent study that explored the role of factors at multiple social-ecological levels on physical IPV in a highly vulnerable sample: 1,112 different-sex couples in which the male partner had recently returned from prison. Results: In fitted structural equation models, local social and structural conditions predict both situational couple violence (SCV) and coercive controlling violence (CCV). However, the influence of local conditions on each type of IPV occurs via different proximal factors. Local conditions predict SCV via hopelessness and predict CCV via post-traumatic stress and dysfunctional conflict. Conclusions: These exploratory findings indicate that local social and structural conditions could promote both SCV and CCV, but via different proximal processes. They suggest that IPV research has much to gain from integrating the distinct theoretical and methodological contributions of scholarship on Johnson’s typology and ongoing inquiry into the broader social ecology of IPV.